Control of Pathogenic Vibrios in Shrimp Aquaculture using Antiinfectives from Marine Natural Products - Selvin, Joseph; Ninawe, A.S.; Meenatchi, R.; Seghal Kiran, G. (Avances en Nutrición Acuicola, 2015)
Mid-culture outbreaks due to pathogenic Vibrio spp. are most common and frequent disease problems encountered in shrimp aquaculture. Literature showed that the decades old shell disease to recent early mortality syndrome are caused by vibrios as primary and/or secondary etiological agents. Poor water quality, deteriorated pond bottom due to over feeding, inadequate farm management, rapid intensification of stocking approaches etc. are major predisposing factors of disease outbreaks. Both reactive and proactive treatment methods are being progressed through R&D efforts, but tangible solution is remain to prevent/control mid-culture outbreaks in shrimp aquaculture. Alternate approaches to replace the use of antibiotics in aquaculture is a highly prioritized research area. Alternate approaches are being widened to explore marine natural products, smart biomolecules such as biosurfactants and poly-hydroxy butyrates (PHB), nanoparticles, quorum quenching molecules, small bioactive peptides and probiotics. The oceans are the single principal bio-resource of halo-metabolites produced by a range of marine organisms such as seaweeds, corals, sponges, molluscs, coelenterates, marine worms, tunicates, bacteria etc. but their utilization as aquaculture drugs are not being exploited. Application of seaweed secondary metabolites in treating shrimp bacterial diseases represents an easy, cost effective and environmentally benign venture for equitable and sustainable shrimp farming. Recently we reported antiadhesive activity of PHB biopolymer against Vibrio alginolyticus and V. harveyi, which were considered as the most significant pathogenic vibrios in the grow-out ponds of giant black tiger shrimp Penaeus monodon. In order to reduce the use of antibiotics, pesticides and other chemicals and to improve the ecological environment of shrimp farms, research is being focused on the potential use of marine probiotic bacteria in shrimp farms to improve water quality by balancing bacterial population in water and reducing pathogenic bacterial load.